DRINKING WATER OF CHERNIGIV AND ITS QUALITY - Smolsky Олександр; Bondar Олена; Kurmakova Ірина; Kotelchuk Андрій; Kotelchuk Леонід (Biota. Human. Technology, 2025)
Purpose of the work. To establish the indicators of drinking water quality (total hardness, bicarbonate alkalinity, content of calcium ions, magnesium ions, chloride ions, ammonium ions, ions Fe2+ and Fe3+, acidity (pH) of the centralized water supply network in Chernihiv. The results were then compared with the normative values by DSTU ISO 6059-2003. Tested water samples were collected at four control points which are part of different aquifer stations that draw water from the Lower Cretaceous and Buchakian horizons. The purpose of this article is to evaluate the current state of water quality in specific sections of the Chernihiv water supply network. Methodology. Water samples were collected from the city's water supply systems by DSTU ISO 5667-4-2003. The indicators analyzed included total hardness, bicarbonate alkalinity, chloride ion content, ammonium ion content, ions Fe2+ and Fe3+content, pH levels. These indicators were assessed using standard methods of chemical and physicochemical (photocolorimetry, potentiometry) analysis. The scientific novelty of this research lies in the comparative analysis of the chemical and physicochemical parameters of water samples collected from control points within different sections of the municipal water supply network. This network sources its water from 1st, 3rd and 5th water-bearing stations that draw from the Lower Cretaceous and Buchaksky aquifers. Conclusions: During a comparative analysis of the chemical and physicochemical parameters of water samples taken from various control points of the municipal water supply network in Chernihiv, that draw from the Lower Cretaceous and Buchaksky aquifers it was found that the standard values for ions Fe2+ and Fe3+ and ammonium ion concentrations were exceeded. These samples were specifically from the water pumping station “Bobrovytsia”.